(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2018)
Background: Shivering is a common problem faced by an anesthesiologist during per-operative period as well as in post-operative period. Objective: The present study was designed to observe the efficacy of tramadol, low dose ketamine and ondansetron in the management of intra-operative shivering after sub arachnoid block. Methodology: This single center, parallel, double blind randomized control trialwas conducted in the Department of Anaesthesia, Analgesia and Intensive Care Medicine at Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh from July 2007 to June 2009 for a period of two (02) years.Patients undergoing surgery with Sub Arachnoid Block, patients with age range from 18 to 60 years, patients from both sexes and ASA class I and class II were selected as study population.After recruitment each subject was allowed to draw one card and grouped accordingly. Group T: Shivering was treated with tramadol. Group K: Low dose ketamine was used to manage shivering. Group 0: Ondansetron was injected for shivering. The patients was also monitored for complications like nausea, vomiting and respiratory depression (defined as respiratory rate <8/minute). Time taken for cessation of shivering was noted for all groups and all patients were watched for recurrence of shivering. Result: A total of 90 (ninety) patients were enrolled in this study of whom thirty (30) patients were enclosed in each group. Among thirty patients in each group. Group T was effective in 27(90%) patients, group K was effective in 21(70%) patients and group O in 20(66.7%) patients with a p value of 0.075. Statistically, though it is not significant but according to the consideration of percentage, Group T is superior to other two groups. Again recurrence of shivering occurred in one patient in Gr.-T, eight (08) person in Gr.-K and three (03) patient in group Gr.-O indicating a p value of 0.024. This equation reflects the lowest statistically significant recurrence of shivering in Group T than others.Out of thirty patients in each group, nausea or vomiting occurred only in 3 patients of T group (10%) respiratory depression occurred in 10 patients (33.3%) of K group only. Conclusion: The efficacy of tramadol is a better option than low dose ketamine and ondansetron in the management of intra-operative shivering after sub arachnoid block. Journal of National Institute of Neurosciences Bangladesh, 2018;4(1): 45-50